2021
DOI: 10.1007/s00468-021-02124-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional quantification of tree architecture from mobile laser scanning and geometry analysis

Abstract: Key message Mobile laser scanning and geometrical analysis revealed relationships between tree geometry and seed dispersal mechanism, latitude of origin, as well as growth. Abstract The structure and dynamics of a forest are defined by the architecture and growth patterns of its individual trees. In turn, tree architecture and growth result from the interplay between the genetic building plans and environmental factors. We set out to investigate whether (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Using the single tree point clouds, several structural attributes were computed. The analysis was restricted to beech in this case study because of known structural differences between the different tree species (Seidel, 2018;Seidel et al, 2019a;Dorji et al, 2021), except for the plot-level complexity calculations. The complexity of each tree was determined by using the algorithm of Seidel (2018) in Mathematica (Wolfram Research, Champaign, IL, United States).…”
Section: Calculation Of Point Cloud Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the single tree point clouds, several structural attributes were computed. The analysis was restricted to beech in this case study because of known structural differences between the different tree species (Seidel, 2018;Seidel et al, 2019a;Dorji et al, 2021), except for the plot-level complexity calculations. The complexity of each tree was determined by using the algorithm of Seidel (2018) in Mathematica (Wolfram Research, Champaign, IL, United States).…”
Section: Calculation Of Point Cloud Attributesmentioning
confidence: 99%
“…Recent studies showed that the box-dimension relates to a number of individual structural attributes of a tree (Seidel et al, 2019a,c) and that it is also responsive to factors affecting tree growth, such as competition (Seidel, 2018;Dorji et al, 2019;Seidel et al, 2019a) and management (Saarinen et al, 2020;Stiers et al, 2020). It was also shown that the box-dimension is related to the seed dispersal strategy of a tree (Dorji et al, 2021). Unsurprisingly, the amount and distribution of the tree organs, as described by the box-dimension, also relate to tree growth (Seidel, 2018;Dorji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the mean D b of the leaf-on tree point clouds was greater than 2 across all study tree species (see Table 1), indicating a possible structural difference between trees in rural versus urban areas. However, rural forest trees growing in more open conditions and facing less competition for light (e.g., in forest gaps and in thinned forest stands), also had larger D b values [13,19,106], in some cases exceeding 2 [107]. This suggests a benefit to having an increased D b with more light and fewer neighbors, but at some level the energy benefits from increased photosynthesis would be minimized due to a high level of self-shading [90].…”
Section: Structural Complexity Of Urban Treesmentioning
confidence: 99%
“…Data from mobile laser scanning (MLS) could also be used to study the WSA of trees covering larger spatial scales if occlusion effects in the point clouds are not significant. According to Dorji et al [82], MLS data can be used to study the structural complexity of trees based on fractal analysis and quantified by the D b metric.…”
Section: Advances In Urban Tree Surface Area Measurementmentioning
confidence: 99%